Disaster response (relief strategies) in Zimbabwe: case of Tokwe Mukosi. - Kufandada, Elton A. (Midlands State University, 2017)
The main thrust of the research was to investigate the effectiveness of disaster response in Zimbabwe. The topic is called disaster response (relief strategies) in Zimbabwe Case of Tokwe- Mukosi. The objectives of the study included identifying and establishing the various roles of different stakeholders, local government, Department of Civil protection, NGOs, Civil Society Organisations etc, in disaster response in Zimbabwe, determining the effects of disasters, establishing an effective plan for better emergency response and also examining the factors impeding effective disaster response in Zimbabwe. Disasters result in dire effects that often leave the affected families in need of humanitarian assistance. These effects include destruction of property, clothes, food, infrastructure, livelihoods and even loss of lives. The after effects of a disaster often impact negatively on the health of the affected communities. These include disease outbreaks like cholera and diarrhea etc. It is the duty of the Department of Civil Protection and other important stakeholders to minimize these effects by responding to the disasters through their different roles. These roles include providing humanitarian aid, coordination of all disaster response activities and making sure that the affected families are safe and well sustained. That is good disaster response. The process of implementing disaster response and its effectiveness varies from country to country. The objectives of the study were also addressed in the empirical evidence of the research whereby the study looked at disaster response from a global, regional and national point of view. The countries in perspective include the USA, Kenya, Mozambique and Sudan. The researcher used the descriptive research design that provided the structure of the research. The population size is 20 000 people and comprise of people from all age groups. The sampling techniques used include convenience sampling for the disaster victim and purposive/ judgemental sampling for the key informant interviews. The sample size is 150 people. The data collection instruments used include questionnaires and interviews. From the findings, the researcher noted that disaster response to the Tokwe- Mukosi flood disaster was affected by a number of factors which include lack of funds, lack of disaster response resource materials, poor community and district structures, poor road networks and resistance or lack of cooperation from the affected families. It also became evident that Chivi RDC department of Community Services is not very instrumental in disaster management in the district, rather, it is the District Administrator who spear head disaster response at district level. Even though the district has a disaster response plan in place, the plan needs periodic updating and testing to ensure optimum response in case of an emergency. It is also recommended that the state should look for more ways to strengthen its relations with Humanitarian and International aid donors so as to reduce the effects of a disaster. This research also revealed the fact that the local community of Nuanetsi Ranch does not know their roles in responding to a disaster. As such, the researcher recommends that more awareness campaigns should be carried out by the Department of Civil Protection together with its supporting partners in ensuring that communities are educated on their duties and roles in disaster response. This can help in reducing the effects of a disaster.